Electrical cardioversion during cryoballoon pulmonary vein isolation predicts long-term ablation success in persistent atrial fibrillation. (24th May 2021) - Boehmer, A; Rothe, M; Soether, CM; Dobre, BC; Abboud, J; Kaess, B; Ehrlich, JR
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cryoballoon pulmonary vein isolation (cryoPVI) is an established option for treatment of atrial fibrillation (AF) but many periprocedural events influencing long-term outcome and procedural safety of ablation remain unclear. In radiofrequency ablation studies, failure to convert to sinus rhythm and electrical cardioversion (ECV) have been associated with increased recurrence rates. In this context, the influence of ECV during cryoPVI on long-term ablation efficacy is unclear. Objective: A prospective comparison of AF recurrence after cryoballoon ablation in patients who were in AF or atrial tachycardia at the beginning of cryoPVI requiring ECV during procedure with patients who underwent ablation therapy without ECV. Methods: We analyzed consecutive patients who underwent cryoPVI in a single-center cohort between 2018 and 2020. Follow-up was performed at 3, 6, 12, 18 and 24 months after ablation. Primary endpoints were: symptomatic AF recurrence for efficacy and bleeding, phrenic nerve injury, stroke or death for safety. Results: 472 consecutive patients who underwent ablation in a single-center cohort were analysed. Mean follow-up time was 15 months. In 195 patients (74 paroxysmal AF vs. 121 persistent AF, age 69 ± 10 years, 57% male, CHA2DS2-VASc 2.6 ± 1.4) at least one ECV was performed following ablation, while no cardioversion was necessary in 277 patients (214 paroxysmal AF vs. 63 persistent AF, age 69 ± 10 years, 55% male, CHA2DS2-VASc 2.7 ± 1.5). After 24 months, primary efficacy endpoint occurrence was significantly higher in persistent AF requiring cardioversion during procedure than for persistent AF without cardioversion and paroxysmal AF with/ without cardioversion (56.1 % vs. 31.2%, 33.6%, 32.9%, log-rank p = 0.009, figure). Primary safety endpoint occurred in form of pericardial effusion or transient phrenic nerve injury in two patients in cardioversion group (1.0%) and three patients without cardioversion (1.1%). No deaths or strokes were observed in either group. Total procedure duration (55.6 ± 17min vs. 57.7 ± 15.9min, P = 0.17) and left-atrial dwell time (39.7 ± 14.9min vs. 42 ± 15.6min, P = 0.11) were similar. Conclusion: In patients with persistent AF, the need for ECV during cryoPVI predicts a poorer long-term outcome during 2-year follow-up. Future studies should focus on this specific patient population.